The Clinical Significance of Breast-only and Node-only Pathologic Complete Response (pCR) after Neoadjuvant Chemotherapy (NACT): A Review of 20,000 Breast Cancer Patients in the National Cancer Data Base (NCDB) - Fayanju, Oluwadamilola M. (Ann Surg, 2018)
OBJECTIVE: To determine whether the association between overall survival (OS) and response to neoadjuvant chemotherapy (NACT) in breast cancer patients varies with tumor subtype and anatomic extent of pathologic complete response (pCR). BACKGROUND: pCR after NACT predicts improved OS in breast cancer, but it is unclear whether pCR limited to the breast or axilla is also associated with OS. METHODS: Women with cT1–3/cN0–1 breast cancer diagnosed 2010–2014 who underwent surgery following NACT were identified in the NCDB and divided into 4 subtypes based on reported hormone receptor (HR) and HER2 status. Kaplan-Meier curves and Cox proportional hazards models were used to estimate OS. Multivariate logistic regression was used to identify factors associated with post-NACT response, defined as upstage (yp stage>clinical stage); no change (clinical stage=yp stage); overall (breast+axilla, ypT0N0), breast-only (ypT0N1/N1mic), or node-only (ypT1–3N0) pCR. RESULTS: Of 33,162 identified patients, 20,265 experienced overall pCR (n=6,370, 19.2%), breast-only pCR (n=494, 1.5%), node-only pCR (n=1,133, 3.4%), no stage change (n=9,641, 29.1%), or upstage (n=2,627, 7.9%). Compared to no stage change, breast-only pCR was associated with improved OS in triple-negative disease (HR=0.58,95%CI=0.37–0.89), and node-only pCR was associated with improved OS in both triple-negative (HR=0.55,95%CI=0.39–0.76) and HR+/HER2- disease (HR=0.54,95%CI=0.33–0.89). For patients achieving overall (breast+axilla) pCR, unadjusted 5-year OS was 0.94 (95%CI=0.93–0.95), with no difference between patients who were cN0 (0.95,95%CI=0.93–0.96) or cN1 (0.94,95%CI=0.92–0.96) at diagnosis. CONCLUSIONS: In node-positive patients, pCR limited to either the breast or axilla predicts survival for select receptor subtypes. In patients achieving pCR in both the breast and axilla, survival is driven by response to NACT rather than presenting cN stage.